Pattern of stroke patients admitted at a tertiary Hospital in Bangladesh - Hassan, M. Mahade; Nandy, Alak; Shafatujjahan; Chowdhury, Adnan Ibrahim; Rahaman, Tarequr; Raihan, M. Kafil Uddin (International Journal of Research in Medical Sciences, 2025)
Background: Stroke is one of the most common causes of mortality and morbidity in Bangladesh. The purpose of the study was to understand the pattern of stroke in a tertiary care hospital in Bangladesh. Methods: This cross-sectional study was carried out from June to November 2023 among diagnosed stroke patients. Convenient sampling was used to select the 60 patients from Chattogram Maa O Shishu Hospital, Bangladesh. A face-to-face interview was conducted using a semi-structured questionnaire. Descriptive analysis and Chi-square test were performed by IBM SPSS software. Results: Among 60 patients, almost half (48.3%) were in the 65–84 age group. Most of the patients had HTN (81.7%) and DM (55%). About 40% of ischemic and haemorrhagic patients had arrived at the hospital before 6 hours. This study also found that only 38% of ischemic stroke patients and 20% of haemorrhagic patients had a good (13–15) GCS score. The NIHSS score was very severe (21-42) among 36% of ischemic stroke patients and 40% of haemorrhagic stroke patients. Vomiting, GCS, headache, convulsion, pulse, and diastolic blood pressure had a significant (p≤0.05) association with stroke. Conclusions: Ischemic stroke was the predominant form of stroke, and a large number of patients arrived at the hospital on time. Rapid initiation of treatment can decrease morbidity and mortality rates significantly. So, a stroke center should be established as soon as possible to save patients’ lives.